Microbiome composition of Drosophila suzukii varies across geographical regions - Medeiros, Matthew J.; Burger, Allexa D.; Price, Donald K.; Yew, Joanne Y. (Frontiers in Ecology and Evolution, 2025)
Drosophila suzukii is a common agricultural pest in numerous parts of the world, costing more than $500 million annually in crop loss in the United States alone. Understanding the genetic and physiological mechanisms underlying its remarkable adaptability has been a major focus for the agricultural industry as well as evolutionary biologists. The microbiome, the community of microbes associated with host organisms, can play a pivotal role in local adaptation by improving host resilience to environmental stress and providing access to new sources of nutrition. Here, we test the hypothesis that the colonization of non-native regions is associated with the incorporation of regionally-specific microbial taxa. We compare the microbiome profiles of wild-caught D. suzukii across five global sites, Asia, Europe, the United Kingdom, North America, and Hawai‘i. We also compare microbial communities of D. suzukii found in Hawai‘i to another local invasive species, D. immigrans, and native Hawaiian drosophilids. Our results reveal that wild-caught D. suzukii from Asia, Europe, the United Kingdom, North America, and the Hawaiian Islands exhibit distinct microbial compositions indicating that the environment is a stronger driver of microbiome composition than species identity. Seven bacterial families were conserved between all wild D. suzukii populations. Within Hawai‘i, non-native D. suzukii bacterial communities differed from those of native Hawaiian Drosophila species as well as non-native D. immigrans. By contrast, fungal microbiome profiles between the Hawaiian Drosophila and two invasive species closely resemble each other. In sum, all populations of D. suzukii in this study contain a subset of conserved bacterial families but also incorporate local bacterial taxa. This strategy may contribute to the rapid range expansion of D. suzukii and enhance its ability to exploit new dietary sources.